Amyloid β protein toxicity mediated by the formation of amyloid-β protein precursor complexes - Lu, Daniel C.; Shaked, Gideon M.; Masliah, Eliezer; Bredesen, Dale E.; Koo, Edward H. (Annals of neurology, 2003)
The amyloid‐β protein precursor, a type 1 transmembrane protein, gives rise to the amyloid β‐protein, a neurotoxic peptide postulated to be involved in the pathogenesis of Alzheimer's disease. Here, we show that soluble amyloid β protein accelerates amyloid precursor protein complex formation, a process that contributes to neuronal cell death. The mechanism of cell death involves the recruitment of caspase‐8 to the complex, followed by intracytoplasmic caspase cleavage of amyloid precursor protein. In vivo, the levels of soluble amyloid β protein correlated with caspase‐cleaved fragments of the amyloid precursor protein in brains of Alzheimer's disease subjects. These findings suggest that soluble amyloid β protein–induced multimerization of the amyloid precursor protein may be another mechanism by which amyloid β protein contributes to synapse loss and neuronal cell death seen in Alzheimer's disease. Ann Neurol 2003;54:781–789